2010
DOI: 10.1111/j.1462-2920.2009.02089.x
|View full text |Cite
|
Sign up to set email alerts
|

Biomass production and energy source of thermophiles in a Japanese alkaline geothermal pool

Abstract: Microbial biomass production has been measured to investigate the contribution of planktonic bacteria to fluxations in dissolved organic matter in marine and freshwater environments, but little is known about biomass production of thermophiles inhabiting geothermal and hydrothermal regions. The biomass production of thermophiles inhabiting an 85 degrees C geothermal pool was measured by in situ cultivation using diffusion chambers. The thermophiles' growth rates ranged from 0.43 to 0.82 day(-1), similar to tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…The growth rate of thermophiles inhabiting an 85 C geothermal pool has been measured by the similar in situ diffusion chamber tool, and recorded a range from 20 to 39 h doubling time under 0.2 mM sulfide in geothermal fluid (Kimura et al 2010). This range was a comparable result determined in 2 mM sulfide in the hydrothermal vent of Hatoma Knoll.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The growth rate of thermophiles inhabiting an 85 C geothermal pool has been measured by the similar in situ diffusion chamber tool, and recorded a range from 20 to 39 h doubling time under 0.2 mM sulfide in geothermal fluid (Kimura et al 2010). This range was a comparable result determined in 2 mM sulfide in the hydrothermal vent of Hatoma Knoll.…”
Section: Discussionsupporting
confidence: 59%
“…It has been applied in deep-sea expeditions for hydrothermal vents, and successfully isolated and/or accumulated novel chemolithotrophic bacteria Reysenbach et al 2000;Takai et al 2003). Of theses several types of in situ chambers, a diffusion chamber is a very useful apparatus for in situ physiological experiments of microbes (Bollmann et al 2007;McFeters and Stuart 1972;Vasconcelos and Swartz 1976), in situ determination of growth rate of phytoplankton (Furnas 1991) and thermophiles in alkaline geothermal pool (Kimura et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Nakabusa hot spring in Japan has been well-documented by geochemists and microbiologists in terms of its well-developed microbial mats (79, 11, 12, 1922, 24, 30, 31, 40). The hot spring water is slightly alkaline (pH 8.3–8.9) and contains sulfide (~0.1 mM), sulfate (~0.1 mM) and low concentrations of organic compounds (0.4 mg L −1 total organic carbon) (24, 30, 31).…”
mentioning
confidence: 99%
“…From the microbial cell density and the carbon content, the cellular carbon content was roughly calculated to be 4.15±0.01 pg of C cell −1 (mean±standard deviation; n=9). The estimated biovolume and cellular carbon content were much higher than those of other natural microbes and bacterial strains (2,9,11,12). Ogawa and Maki (19) reported that sulfur-turf microbial mats produce gelatinous extracellular polysaccharides.…”
mentioning
confidence: 99%
“…The growth rates ranged from 0.45 to 0.52 h −1 with an overall average of 0.48 h −1 ( Table 2). These growth rates were at least an order of magnitude higher than those of the phototrophic and heterotrophic bacterioplankton that inhabit marine environments (10,16,21), as well as the thermophiles that inhabited a geothermal pool of 85°C (9). From the growth rates determined in this study, the doubling time was calculated to range from 80 to 92 min.…”
mentioning
confidence: 99%